PENGARUH MODEL PEMBELAJARAN KOOPERATIF STAD TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS VII SMP NEGERI 1 SUNGAI BEREMAS - Rahmah, Izzati (Jurnal Edukasi dan Penelitian Matematika, 2024)
Achieving learning objectives characterises good learning outcomes. Grade VII students at SMPN 1 Sungai Beremas still performed poorly in the first summative assessment in the 2023/2024 academic year.  This study aims to compare and contrast the conventional model with the Student Team Achievemen Division (STAD) type cooperative learning model to determine whether the STAD model produces more optimal results for grade VII at SMP Negeri 1 Sungai Beremas. This study was a pseudo-experiment, and the control group was designed using a non-equivalent posttest. The basic random sample procedure was used for sampling. Learning outcome test was used in the instrument. With a p-value = 0.000, H0 was rejected. Therefore, in grade seven at SMP Negeri 1 Sungai Beremas, students who used the STAD model to learn mathematics outperformed their counterparts who used the conventional model.Keywords– STAD, Learning outcomes, Conventional learning